Supporting people with type 2 diabetes in effective use of their medicine through mobile health technology integrated with clinical care (SuMMiT-D Feasibility): a randomised feasibility trial protocol - Farmer, A; Allen, J; Bartlett, K; Bower, P; Chi, Y; French, D; Gudgin, B; Holmes, E; Horne, R; Hughes, D; Kenning, C; Locock, L; et al. (BMJ, 2019)
Introduction: Type 2 diabetes is common, affecting over 400 million people worldwide. Risk of serious complications can be reduced through use of effective treatments and active self-management. However, people are often concerned about starting new medicines and face difficulties in taking them regularly. Use of brief messages to provide education and support self-management, delivered through mobile phone-based text-messages can be an effective tool for some long-term conditions. We have developed messages aiming to support patients’ self-management of type 2 diabetes in the use of medications and other aspects of self-management, underpinned by theory and evidence. The aim of this trial is to determine the feasibility of a large-scale clinical trial to test the effectiveness and cost-effectiveness of the intervention, compared to usual care. Methods and analysis: The feasibility trial will be a multi-centre individually randomised, controlled trial in primary care recruiting adults (≥35 years) with type 2 diabetes in England. Consenting participants will be randomised to receive short text-messages three times a week with messages designed to produce change in medication adherence or non-health related messages for six months. The aims are to test recruitment methods, retention to the study, the feasibility of data collection and the mobile-phone and web-based processes of a proposed definitive trial and to refine the text messaging intervention. The primary outcome is the rate of recruitment to randomisation of participants to the trial. Data, including patient reported measures, will be collected online at baseline and the end of the six-month follow-up period. With 200 participants (100 in each group), this trial is powered to estimate 80% follow up within 95% confidence intervals of 73.8% to 85.3%. The analysis will follow a pre-specified plan. Ethics and Dissemination: Ethics approval was obtained from the West of Scotland Research Ethics Committee 05. The results will be disseminated through conference presentations, peer-reviewed journals and will be published on the trial website: www.summit-d.org.